Comparative Analysis of Diagnostic Methods for Tuberculosis in an HIV-Positive Patient with Acute Respiratory Failure - Parra-Vera, Henry Junior; Buele-Chica, Dayci; Farfan Cano, Galo Guillermo; Solorzano-Bravo, Maria (Futurity Medicine, 2024)
Aims: To compare the diagnostic utility of TB LAM testing against the gold standard BAL with GeneXpert in a critically ill patient with advanced HIV. Methodology: A case report of a 28-year-old man with severe respiratory distress, confirmed HIV (CD4 count of 12 cells/cc³), and negative TB LAM test. Initial treatments included caspofungin, ampicillin-sulbactam, and cotrimoxazole forte. Imaging showed alveolar consolidations, and blood cultures were negative. Results: Notwithstanding the application of empirically validated therapeutic interventions targeting tuberculosis (TB), fungal infections, and Pneumocystis jirovecii, the patient’s clinical status progressively deteriorated, culminating in fatality. Scientific Novelty: This case highlighted the need for combining urine LAM testing with GeneXpert for accurate TB diagnosis in advanced HIV patients. Conclusion: GeneXpert is essential for confirming TB and rifampicin resistance, while urine LAM should be complemented with additional tests when clinical suspicion remains high. Incorporating these assessments elevates diagnostic precision and improves patient prognoses.